Controlling Electrochemically Induced Volume Changes in Conjugated Polymers by Chemical Design: from Theory to Devices. (17th April 2021) - Moser, Maximilian; Gladisch, Johannes; Ghosh, Sarbani; Hidalgo, Tania Cecilia; Ponder, James F.; Sheelamanthula, Rajendar; Thiburce, Quentin; Gasparini, Nicola; Wadsworth, Andrew; Salleo, Alberto; Inal, Sahika; Berggren, Magnus; et al.
Abstract: Electrochemically induced volume changes in organic mixed ionic‐electronic conductors (OMIECs) are particularly important for their use in dynamic microfiltration systems, biomedical machinery, and electronic devices. Although significant advances have been made to maximize the dimensional changes that can be accomplished by OMIECs, there is currently limited understanding of how changes in their molecular structures impact their underpinning fundamental processes and their performance in electronic devices. Herein, a series of ethylene glycol functionalized conjugated polymers is synthesized, and their electromechanical properties are evaluated through a combined approach of experimental measurements and molecular dynamics simulations. As demonstrated, alterations in the molecular structure of OMIECs impact numerous processes occurring during their electrochemical swelling, with sidechain length shortening decreasing the number of incorporated water molecules, reducing the generated void volumes and promoting the OMIECs to undergo different phase transitions. Ultimately, the impact of these combined molecular processes is assessed in organic electrochemical transistors, revealing that careful balancing of these phenomena is required to maximize device performance. Abstract : Control of the electrochemical expansion in organic mixed ionic‐electronic conductors (OMIECs) is of paramount importance for several electronic applications including soft robotics, dynamic microfiltration systems, organic electrochemical transistors and many more. Herein the effects of chemical design on the swelling behavior of a series of OMIECs is evaluated through a combined experimental and computational simulation approach.